Afterall : A Journal of Art, Context and Enquiry. (Londen Valencia (California) : Central Saint Martins College of Art and Design California Institute of the Arts, 1999)
Published twice a year, each issue of Afterall journal includes in-depth considerations of the work of contemporary artists, as well as essays on art history and critical theory. (https://www.afterall.org/publications/)
Https://www.afterall.org
Https://www.journals.uchicago.edu/loi/aft (login)
Engels
Tijdschriften